Development and validation of a simple method for the extraction and quantification of crisaborole in skin layers. (29th August 2019) - Demurtas, Anna; Pescina, Silvia; Nicoli, Sara; Santi, Patrizia; Padula, Cristina
Abstract: Crisaborole is a boron compound recently approved by the US Food and Drug Administration as a 2% ointment for the treatment of mild to moderate atopic dermatitis. This work describes a simple method for the quantification of the drug in the skin layers at the end of in‐vitro permeation experiments. Chromatographic separation was carried out on a reverse‐phase C18 column using a mixture of trifluoroacetic acid 0.05%–acetonitrile (55:45, v/v) as mobile phase, pumped at 1 ml/min. Column temperature was 35°C and UV detection was performed at 250 nm. The method was linear in the range of concentration from 0.06 to 6 μg/ml ( R 2 = 1) and was selective, precise and accurate. Depending on the solvent used, the LOQ ranged from 0.014 to 0.030 μg/ml and the LOD from 0.005 to 0.010 μg/ml. The extraction from all the skin layers was quantitative. The developed method was successfully tested in an in‐vitro permeation study, proving to be an effective tool in the development of new formulations containing crisaborole.